World economy taking a turn for the better - Günter Großer; Günter Weinert (Intereconomics, 1994)
After a three-year slowdown in the world economy, unemployment in the industrial countries is again almost as high as at the end of the recession in the early eighties. Any improvement will be dependent on a distinct resurgence of economic activity. With the recovery in the USA gaining greater momentum and the recession in Western Europe evidently coming to an end, the outlook in recent months has brightened. Will expansionary forces prevail in 1994?
Keywords: 330; Economic Trends